The Effect of Credit Circulation, Loan to Deposit Ratio (LDR), and Interest Rate on Return On Assets (ROA) Due to Non-Performing Loan (NPL) on Credit Unions in Indonesia - Sabinus Beni; Windhu Putra; Nurul Bariyah (International Journal of Multi Discipline Science, 2023)
Credit Unions or commonly known as CUs are quite developed in Indonesia, especially on the island of Kalimantan. One of the Credit Cooperative Centers that house Primary CU in Indonesia has service areas in 34 Provinces in Indonesia, namely the Credit Union Credit Cooperative Center Indonesia (PUSKOPCUINA). The CU under the auspices of the PUSKOPCUINA movement has grown very well and has become a reference for CUs in Indonesia in terms of development and empowerment. CU's contribution is still not significant in boosting national economic growth, so more comprehensive research is needed. The development of CU in Indonesia is inseparable from the development of the Return On Assets (ROA) contained in the CU. The Kalimantan credit union movement is under the auspices of PUSKOPCUINA which has different regional and cultural characteristics. This is what researchers see as necessary to research the Effect of Outstanding Credit, Loan to Deposit Ratio (LDR), and Loan Interest Rates on Return On Assets (ROA) Due to Default Credit (NPL) at Credit Unions in Indonesia. The research objective was to test and formulate solutions to problems arising from the influence of Outstanding Credit, Loan to Deposit Ratio and Loan Interest Rates on Return On Assets due to Non-Performing Loans. The method used was quantitative research with Path Analysis in the data processing. The research population was the CU movement in Indonesia with a sample of 40 CUs under PUSKOPCUINA. The data used was outstanding credit data, Loan to Deposit ratio, non-performing loans, loan interest rates, and return on assets of 40 CU at PUSKOPCUINA in 2015-2019 with the model used to analyze panel data called the panel data model analyzed using Path Analysis. The results of the study showed that the Loan to Deposit ratio, non-performing loans, and loan interest rates had a significant effect on the return on assets of CUs in Indonesia.